Priorities for the Use of Computer Programs in Landscape Design (Journal of Architectural Design, 2022)
In the past, landscape experts had not thought about the possibility of using computer software in this area. Is it possible to convey project ideas based on the inner experiences and feelings of the designer using computer programs, or is it possible to do it only with the help of manual graphics (pencil, watercolor, etc.)? It was hard to imagine. Today, it is difficult to work in any field without computer programs, especially in landscape design, where computer programs are widely used. Especially in the requirements of landscaping competitions, the concept of the design stages of the field has become a condition for presentation in computer programs.